Project management - Maylor, Harvey; Turner, Neil (UK: Pearson, 2022)
"Project Management is a fast-moving and increasingly widespread discipline with record numbers of practitioners now gaining professional qualifications. Delivering projects on time and within budget is critical to business success and the skill, therefore, is highly valued in graduates and managers alike. Highlights of this fifth edition include: Brand new chapters on Planning and scheduling, Advanced Project Thinking (APT), Procuring, contracting, and working with supply chains. New scene-setting vignettes open each chapter, such as the Range Rover Sport and the Nobel Peace Prize to Nadia Murad and Denis Mukwege Project Management in Practice case studies at the end of each chapter include Heathrow Terminal 5 and the Rescue of Crossrail New and revised Real World examples throughout all chapters A critical appraisal of project management, drawing on recent research and new and original models and frameworks Project Management is written for students on undergraduate, masters and MBA programmes, as well as for corporate training and for professionals practising in a dynamic and fast-developing field"--
Includes bibliographical references and index.
Keywords: Project management